2023
DOI: 10.1186/s13020-023-00716-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the anti-hyperuricemia effect of TongFengTangSan (TFTS) by UPLC-Q-TOF/MS-based non-targeted metabonomics

Abstract: Background TongFengTangSan (TFTS) is a commonly used Tibetan prescription for gout treatment. Previously, TFTS (CF) was confirmed to have a significant uric acid-lowering effect. However, the anti-hyperuricemia mechanisms and the main active fractions remain unclear. The current study aimed to investigate the anti-hyperuricemia mechanism using metabolomics and confirm the active CF fraction. Methods The hyperuricemia model was established through i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…The possible pathways for TAP affecting PO-induced HUA were “neuroactive ligand–receptor interaction”, “purine metabolism”, “protein digestion and absorption”, “propanoate metabolism”, and “ABC transporters”, among which purine metabolism had the highest number of metabolites and the highest enrichment significance. It was suggested that TAP mainly regulated purine metabolism to alleviate HUA, corresponding to the previous results. ,, Besides, the difference abundance score map of the pathway (Figure B) also confirmed that the downregulation of purine metabolism and ABC transporters contributed to the effect of HUA.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The possible pathways for TAP affecting PO-induced HUA were “neuroactive ligand–receptor interaction”, “purine metabolism”, “protein digestion and absorption”, “propanoate metabolism”, and “ABC transporters”, among which purine metabolism had the highest number of metabolites and the highest enrichment significance. It was suggested that TAP mainly regulated purine metabolism to alleviate HUA, corresponding to the previous results. ,, Besides, the difference abundance score map of the pathway (Figure B) also confirmed that the downregulation of purine metabolism and ABC transporters contributed to the effect of HUA.…”
Section: Resultssupporting
confidence: 84%
“…It was suggested that TAP mainly regulated purine metabolism to alleviate HUA, corresponding to the previous results. 36,53,58 Besides, the difference abundance score map of the pathway (Figure 8B) also confirmed that the downregulation of purine metabolism and ABC transporters contributed to the effect of HUA.…”
Section: Effects Of Tap On Serum Andsupporting
confidence: 52%
“…The dry extract was then reconstituted in 1 mL methanol, and centrifuged for 10 min at 14 000 g at 4 °C. The supernatant was then filtered and subjected to LC–MS analysis [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dry extract was then reconstituted in 1 mL methanol, and centrifuged for 10 min at 14 000 g at 4°C. The supernatant was then ltered and subjected to LC-MS analysis [12].…”
Section: Animal Treatment and Collection Of Brain Samples For Metabol...mentioning
confidence: 99%